MODEL PROCESS ORIENTED GUIDED INQUIRY LEARNING (POGIL) BERBASIS BUDAYA MELAYU SEBAGAI STRATEGI PENDIDIKAN KARAKTER DAN SOSIAL-EMOSIONAL DI ERA DIGITAL - Anim, Anim; Surya, Edy; Syahputra, Edi (Prosiding Temu Ilmiah Nasional Guru, 2026)
The rapid development of digital technology has significantly transformed the interaction patterns of Generation Z and Generation Alpha, particularly in terms of character and socio-emotional aspects. Today’s learners tend to be more individualistic, easily distracted, and demonstrate decreased empathy and social interaction skills. This condition demands innovative learning strategies that not only emphasize academic achievement but also strengthen character and socio-emotional competencies. This study aims to examine the effectiveness of the POGIL-BBM (Process Oriented Guided Inquiry Learning Based on Malay Culture) model in fostering students’ character values and socio-emotional skills in the digital era. Using a quasi-experimental pretest–posttest control group design, the study involved 64 seventh-grade students from SMP Swasta Muhammadiyah 22 Kisaran. The instruments used included a character questionnaire, a socio-emotional scale based on the CASEL framework, and an observation sheet of learning implementation. The results indicated a significant improvement in character dimensions—honesty, responsibility, and cooperation—with an N-gain of 0.68, compared to 0.34 in the control group. Socio-emotional skills also increased by 21.5% in the experimental class, much higher than 9.8% in the control group. The t-test (p < 0.05) confirmed a significant difference between the two groups. Thus, the POGIL-BBM model is effective in strengthening students’ character and socio-emotional development through the integration of Malay cultural values that foster togetherness and local identity.